Boronic Acid-Containing 3H- pyrazolo[4,3-f]quinoline Compounds as Dual CLK/ROCK Inhibitors with Anticancer Properties - Neetu Dayal; Riddhi Chaudhuri; Kofi Simpa Yeboah; Nickolas R. Brauer; Herman O. Sintim (Pharmaceuticals)
Background: The protein kinases CLK and ROCK play key roles in cell growth and migration, respectively, and are potential anticancer targets. ROCK inhibitors have been approved by the FDA for various diseases and CLK inhibitors are currently being trialed in the clinic as anticancer agents. Compounds with polypharmacology are desired, especially in oncology, due to the potential for high efficacy as well as addressing resistance issues. In this report, we have identified and characterized novel, boron-containing dual CLK/ROCK inhibitors with promising anticancer properties. Methods: A library of boronic acid-based CLK/ROCKi was synthesized via Povarov/Doebner-type multicomponent reactions. Kinase inhibition screening and cancer cell viability assays were performed to identify the hit compounds. To gain insights into the probable binding modes of the compounds to the kinases, docking studies were performed. Cell cycle analysis, qPCR and immunoblotting were carried out to further characterize the mode(s) of action of the lead candidates. Results: At 25 nM, the top compounds HSD1400 and HSD1791 inhibited CLK1 and 2 and ROCK2 at greater than 70%. While HSD1400 also inhibited CLK4, the C1 methylated analog HSD1791 did not inhibit CLK4. Antitumor effects of the top compounds were evaluated and dose–response analysis indicated potent inhibition of renal cancer and leukemia cell growth. Immunoblotting results indicated that the top compounds induce DNA damage via upregulation of p-H2AX. Moreover, flow cytometry results demonstrated that the top compounds promote cell cycle arrest in the renal cancer cell line, Caki-1. qPCR and immunoblotting analysis upon HSD1791 dosing indicated suppression of cyclin D/Rb oncogenic pathway upon compound treatment. Conclusions: Novel boronic acid-containing pyrazolo[4,3-f]quinoline-based dual CLK/ROCK inhibitors were identified. The so-called “magic methylation” design approach was used to tune CLK selectivity. Additionally, the findings demonstrate potent in vitro anticancer activity of the lead candidates against renal cancer and leukemia. This adds to the growing list of boron-containing compounds that display biological activities.